An exploration of current and future vector-borne disease threats and opportunities for change - Hiscox, Alexandra; Jones, Robert T.; Dennehy, Jessica; Dyall, Will; Paris, Laura; Spencer, Freya I.; Keating, Fiona; Seelig, Frederik; Narendran, Abhinandan; Das, Avijit; Logan, James G. (Frontiers in Public Health, 2025)
Vector-borne diseases, including dengue, threaten the health and livelihoods of over 80% of the world’s population, particularly in tropical and subtropical regions. Environmental, ecological, climatic, and socio-economic factors are expected to drive increased transmission, emphasizing the need to identify key threats and prioritize strategies for control. We examined drivers, challenges and potential solutions with global experts, using Brazil and India as case studies. Both countries face rapid population growth, unplanned urbanization and increased exposure to animal reservoirs alongside unique surveillance and control challenges. We advocate for improvements in surveillance systems and capacity, investment in sustainable vector control tools, leveraging of artificial intelligence for outbreak prediction, and fostering public-private partnerships to develop innovative interventions. A multifaceted approach, combining community-led initiatives with advanced technologies, is essential to reducing the burden of vector-borne diseases and preventing future epidemics.